Hubungan frekuensi menyikat gigi dan konsumsi makanan kariogenik dengan kejadian karies gigi molar pertama permanen pada anak Sekolah Dasar usia 8-12 tahun Di Desa Pertima, Karangasem, Bali - I Kadek Pendi Aprinta; Mia Ayustina Prasetya; I Made Ady Wirawan (School of Dentistry Faculty of Medicine Udayana University, 2018)
Caries is a demineralization process or destruction of the organic matrix of teeth by a bacterial infection that produces lactic acid. The first permanent molars have the highest prevalence of caries in permanent teeth among others. The purpose of this experiment was to determine the relationship of the frequency of tooth brushing and frequency of consumption of cariogenic foods with the incidence of dental caries first permanent molars in primary school children aged 8-12 years in Pertima village, Karangasem, Bali. Methods: The study design used cross-sectional analytic. Samples were primary school children aged 8-12 years taken from Pertima SD 1, SD 2 Pertima, Pertima SD 3, and SD 4 Pertima, Pertima village, Karangasem, Bali. Sampling techniques using simple random sampling of 107 children. The first permanent molar tooth samples were examined and classified into groups caries and non caries. Respondents whom parent or guardian samples are given a questionnaire to record the frequency of tooth brushing and consumption of cariogenic food for 3 days. Test data analysis using Chi Square. Result: There are 72 children (67.3%) with caries in first permanent molars. The analytical test showed a value p = 0.001 for brushing frequency relationship with the incidence of dental caries of first permanent molars and for cariogenic food consumption frequency relation with the incidence of dental caries of first permanent molars showed p = 0.896. Conclusion: There is a relationship between the frequency of tooth brushing and caries incidence of first permanent molars and there was no correlation between the frequency of consumption of cariogenic foods with the incidence of dental caries first permanent molars in primary school children aged 8-12 years in Pertima village, Karangasem, Bali.